Social-psychological training as method of forming professional competences in Universities of Russia - LAZAREVA, Ylia (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
This article covers the use of social-psychological training, as an active teaching method in the educational process in higher educational institutions of the Russian Federation.